Validation of Genotyping by Sequencing Using Transcriptomics for Diversity and Application of Genomic Selection in Tetraploid Potato - Caruana, B. M.; Pembleton, L. W.; Constable, F.; Rodoni, B.; Slater, A. T.; Cogan, N. O. I. (Frontiers in Plant Science, 2019)
Potato is an important food crop due to its increasing consumption and uses in production worldwide. With the growing as a result there is demand for varieties with improved traits and characteristicsproduction, breeders must continually develop new germplasm. However, breeding improved varietiesthis process is long is a long process and relies heavily on phenotypic evaluation, dated molecular techniques and has little emphasis on modern genotyping approaches, resulting in 10-15 years of evaluation and selection before commercialisation. Few mMolecular markers have been developed for important traits but most of these are for disease and pest resistance, resulting in initial limited marker assisted selection in breeding. This study has evaluated and implemented a high-throughput transcriptome sequencing method (Malmberg et al. 2018) to genotype an Australian relevant collection of commercial cultivars, analyse the genomic structure of the available cultivars and evaluate the potential of genomic selection on highly heritable traits. Identification of high quality SNPs and SNP distribution across the genome were examined using standard bioinformatic pipelines. Analysis of the genetic diversity of all 184 cultivars was performed. Custom bioinformatic pipelines were developed for the prediction of allelic dosage in the potato transcript data. As a result, a large number of SNP markers were identified and filtered to generate a high-quality subset that was then combined with historic phenotypic data from previous breeding efforts to assess the approach for genomic selection. Genomic selection potential was predicted for highly heritable traits and the approach demonstrated advantages over the previously used technologies in terms of markers identified as well as costs incurred. The high-quality SNP list also provided acceptable genome coverage which demonstrates its applicability for much larger future studies. This SNP list was also annotated to provide an indication of function and will serve as a resource for the community in future studies. Genome wide marker tools will provide significant benefits for potato breeding efforts and the application of genomic selection will greatly enhance genetic progress.